Representations of a high-quality system of undergraduate education in English higher education policy documents - Ashwin, Paul; Abbas, Andrea; McLean, Monica (Taylor & Francis, 2015)
This article examines the ways in which a high-quality system of undergraduate education is represented in recent policy documents from a range of actors interested in higher education. Drawing on Basil Bernstein's ideas, the authors conceptualise the policy documents as reflecting a struggle over competing views of quality that are expressed through pedagogic discourses. They identify two pedagogic discourses: a dominant market-oriented generic discourse and an alternative discourse that focuses on transformation. They argue that the market-oriented generic discourse is dominant because it is more coherent and more consistently presented than the alternative discourse, which is much more fractured. In conclusion, they argue that refocusing the alternative discourse of quality around students' relations to academic knowledge may offer a way in which to bring the different actors from the higher education field together in order to form a stronger, more cohesive voice.